Evaluation of clinical efficacy of dydrogesterone in hormonal replacement therapy - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Dydrogesterone is a highly selective progestin freed from many side-effects characteristic for this type of drugs. The authors presented clinical and metabolic effects of its application in menopausal women in view of the risk of breast cancer, vaginal bleeding control, impact on endometrium, lipid profile, cardiovascular risk, and mineral bone density. The positive influence on the above parameters makes dydrogesterone a good alternative to other progestins administered as part of the hormone replacement therapy.